EVALUATION OF INTEGRITY ZONE DEVELOPMENT TOWARDS A CLEAN SERVING BUREAUCRATIC AREA (WBBM) IN THE NORTH KALIMANTAN PROVINCIAL GOVERNMENT - Aziz, Luthfi; Hanafi, Imam; Danar, Oscar Radyan (Faculty of Administrative Science, Universitas Brawijaya, 2023)
The development of the Integrity Zone in the North Kalimantan Provincial Government has been stated in the RPJMD 2021-2026 as the mandate of Perpes 81/2010 concerning the Grand Design of Bureaucratic Reform, with the mission of Realizing a Clean and Authoritative North Kalimantan Provincial Government. It has established the Work Culture of Integritas, Komitmen, Hasanah, Loyalitas, Akuntabitas, Semangat and Motivasi (IKHLAS) as a guideline for every employee. Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) of North Kalimantan Province was appointed as the Pilot Project for the construction of the Integrity Zone, where it launched a declaration of Integrity Zone development in 2018, in 2020 it received the WBK predicate. Starting in 2022, it is proposed to obtain the title of WBBM. This study aims to evaluate the Integrity Zone development towards WBBM using qualitative methods located in the North Kalimantan Provincial Government. Data collection techniques by means of observation, document study, and triangulation. Data analysis through data collection and conclusion drawing. The results of the internal evaluation have fulfilled 7 (seven) criteria towards WBBM with a Corruption Perception Survey Score of 15.79 while the Service Quality Perception Score is 15.79, but there are still shortcomings, namely monitoring and evaluation activities have not been periodic, implementation of SOP and SPBE has not been maximized, Competency-Based Employee Development has not been maximized, and the Whistle-Blowing System and Conflict of Interest Handling have not been maximized. On the basis of the evaluation results, recommendations can be given, namely; Commitment of all Stakeholders, Increased human resource capacity, Use of information technology, Monitoring and Evaluation carried out periodically, Whistle-Blowing System and Conflict of Interest Handling carried out periodically and periodic Satisfaction Assessment Surveys.